KUALITAS KOMPTENSI DAN PROFESIONAL GURU SEKOLAH MINGGU - Frans Pantan; Triyastuti Wuryandari; Benyamin Fadmandarian Kadang (Bethel Press, 2023)
This study aims to analyze the quality of competence and professionalism of Sunday School teachers in addressing the challenges of children’s faith education in the digital era. Employing a descriptive qualitative approach, data were collected through interviews, classroom observations, and documentation in local churches. The findings reveal that Sunday School teachers possess adequate biblical knowledge, yet their pedagogical skills and use of creative media remain limited. Their professionalism is reflected in high dedication, service commitment, and spiritual integrity, but weaknesses persist in lesson preparation and classroom management. The main challenges identified include the lack of formal training, the absence of a structured curriculum, insufficient learning facilities, and the influence of digital culture on children’s learning patterns. The implications highlight the need for systematic and continuous church-led training, including pedagogical development, media provision, and regular teacher evaluation. Enhancing teacher competence and professionalism is thus crucial to ensuring the effectiveness of children’s faith education.